Experimental Study on the Flexural Performance of Parallel Strand Bamboo Beams - Aiping Zhou; Yuling Bian (The Scientific World Journal)
Searching for materials to provide proper housing with less emission and low energy becomes an urgent demand with the ever-growing population. Bamboo has gained a reputation as an ecofriendly, highly renewable source of material. Parallel Strand Bamboo (PSB) is a new biocomposite made of bamboo strips which has superiority performances than wood products. It has attracted considerable interests as a sustainable alternative for more traditional building materials. But the mechanical performance study of PSB as construction materials is still inadequate. Also, the structural behavior of PSB is not quite understood as conventional construction materials, which results in the difficulties to predict the performances of PSB structural members. To achieve this purpose, 4-point bending experiments for PSB beams were carried out. The flexural performances, mode of failure in bending, and the damage mechanism of PSB beams were investigated in this paper.